INNOVATIVE METHODS FOR STUDYING THE INFLUENCE OF EDAPHIC ENVIRONMENTAL FACTORS ON PLANT LIFE - Gubasheva, B. E.; Khassenova, M. A. (Ғылым және білім №3, 2020)
Our research showed that at present, our country is undergoing significant changes in the national education policy. This is due to the transition to the position of personality-oriented pedagogy. The tasks of the educational process include the disclosure of the potential of all participants, the manifestation of their creative abilities in educational activities. Various innovative methods and technologies are used in educational institutions to solve these problems. Innovative learning is considered as a tool for organizing the ways of knowledge used in the activities of subjects of the educational process.
Keywords: рк; научный журнал; периодическое издание; отечественное издание; педагогика; инновационные технологии; innovative technologies; individual and collective abilities; integration; information